Relating pancreatic ductal adenocarcinoma tumor samples and cell lines using gene expression data in translational research - Shuaichen, Liu; Guangyi, Wang (Cellular and Molecular Biology, 2018)
Cancer cell lines are useful tools to study cancer biology. Choosing proper cell lines based on experimental design for different experiments is vital. Relating tumors and cell lines, and recognizing their similarities and differences are thus very important for translational research. Abundant online databases with genomic and expression profile are suitable resources for conducting the assessment. Pancreatic ductal adenocarcinoma (PDAC) is a severe cancer with grim prognosis. Current effective treatments of PDAC remain limited. In this study, we compared the gene expression profile of 178 PDAC tumor samples from The Cancer Genome Atlas and 44 pancreatic cancer cell lines from Cancer Cell Line Encyclopedia. We showed that all pancreatic cancer cell lines resemble PDAC tumors but the correlation is different. Our study will be used to guide the selection of PDAC cell lines.